Improving the Management of the Housing and Utilities System (Journal of Architectural Design, 2023)
The article provides an analysis of the current state of housing and communal services, development programs for this industry. The problems of successful development of housing and communal services are identified, the main directions for improving the management of the development of housing and communal services are outlined. And also given information about the goals of reforming the housing and communal services.